ISU SOSIAL DAN ETIKA DALAM SISTEM INFORMASI DAN TEKNOLOGI INFORMASI DALAM PERSPEKTIF PENDIDIKAN - Soares, Inacio Antonio (Madani Institute : Jurnal Politik, Hukum, Ekonomi, Pendidikan dan Sosial-Budaya, 2025)
The development of information systems and information technology (IS/IT) has brought about significant changes in the world of education. IS/IT enables educational institutions to adapt to modern demands, accelerate administrative processes, and enrich learning methods through digital technology. However, behind this extraordinary progress, there are social and ethical challenges that should not be ignored. This study aims to explore various social and ethical issues related to the use of IS/IT in education, including data privacy, information security, inequality in digital access, and responsible technology use. The method used in this research is a literature review with a descriptive-qualitative approach. The results of the study indicate that the application of information technology in education must be accompanied by a deep understanding of social and ethical aspects so that the technology can provide maximum benefits without causing negative impacts